Theoretical cross-sections of deuteron-induced reaction on natural chromium by EMPIRE code for the production of 52Mn, 54Mn, 51Cr and 48V. Issue 11 (2nd December 2021) - Hasan, Glara; Nury, Edrees; Bianchi, Francesca; Manenti, Simone; Groppi, Flavia
Abstract : Manganese-52 ground ( 52g Mn) is a positron emitter and its beneficial properties make it a strong candidate for positron emission tomography (PET) imaging. Furthermore, the PET isotope 52g Mn has been proposed as a suitable candidate for combination with proteins and antibodies. Moreover, Mn 2+ has a paramagnetic property, thus the Mn isotope is ideal for use in bimodal PET/magnetic resonance (MR) images as a traceable nuclide, that can provide anatomical, molecular and physiological information of tissues. In this work, the theoretical calculation of the cross-section to produce 52 Mn based on EMPIRE 3.2.2 code was carried out, focusing the attention on the optimization of the code parameters. The calculated cross-sections, obtained considering the effect of different level density models of the code, were compared with the experimental ones, to produce 52 Mn isotopes by deuteron beam irradiation in the energy range up to 35 MeV on nat Cr target. At the same time, the co-produced 54 Mn, 51 Cr and 48 V from nat Cr(d, X) nuclear reactions have been investigated. The results are also compared with the data taken from the online TENDL library of different versions.